Kinetika Kadar Air dan Persentase Rendemen Kompos Berbahan Baku Feses Sapi Potong yang Diperkaya Azolla Sp - Pantura Pantura; Agustinah Setyaningrum; Pambudi Yuwono (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Background. The research entitled kinetics of water content and percentage of compost yieldmade from beef cattle feces enriched with Azolla sp was carried out on August 3 to August 28 at UD Sapi Amanah Farm (Beef and sheep fattening), Karang Gintung village,Sumbang sub-district, Banyumas district, and Laboratory of Animal Foodstuff Science, Faculty of Animal Husbandry, Jenderal Soedirman University, Purwokerto. The purpose of this study was to assess the kinetics of water content during composting, determine the moisture content in the compost and the yield were beef cattle feces compost enriched with Azolla sp. Materials and methods. The treatments given in this study were P0 (control), and P1 addedAzolla sp at control (P0) by 10%. The method used in this research was experimental. Data were analyzed by Repeated Measure Analysis of Variance (RMA) for moisture content and data to determine the addition of Azolla sp to compost yield were analyzed by t Test. The variables measured were kinetics of water content and percentage of compost yield. Results. The result showed water the kinetics was the water level at the end of composting was still above the SNI standard, namely P0 was 55.739 ± and P1 was 56.554 ± The yield mean at P0 was 60.7617 ±